The Gamifying Teaching Elementary English: Word Search Game to Reach Vocabulary Mastery: - Devi Novita Sari Simatupang; Tatum Derin (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
The purpose of the research is to find out whether there is any significant effect of the word search game compared to the board game towards the students’ vocabulary mastery at the fourth grade SD Swasta Karya Tani Kandis. The design used in this research is experimental research. The location for this research was at SD Swasta Karya Tani Kandis. The vocabulary test was used to find out the students’ ability in vocabulary. The result of this research shown that the data obtained from the students’ pre-test to find the homogeneity to see the equal ability from both classes. and post-test scores of experimental classes 1 and 2 to know the different scores of two experimental classes. The test was to answer the questions based on the vocabulary test. Before treatment, the researcher gave the pre-test to IVA (experiment class 1) and IVB (experiment class 2). The researcher taught within 6 (Six) meetings including pre-test and post-test. Based on the data analysis it can be seen that Sig < 0,000. The value of sig (2-tailed) was 0.03 and it was lower than significant probabilities 5% (P< 0.05) in post-test experimental classes 1 and 2. Furthermore, there is a significant effect of using Word Search Game toward students’ vocabulary mastery fourth grade SD Swasta Karya Tani Kandis between experimental groups 1 and 2. In conclusion, there was a significant effect of using Word Search Game toward students’ vocabulary mastery.